Wildflower pollen quality in roadside habitats, with particular emphasis on Hedera helix - Aoife McMullin; Paul Hamilton (SURE Journal: (Science Undergraduate Research Experience Journal))
The quality of air is of more significance today than ever before. Human population growth and pollutants emitted through fossil fuel consumption put pressures on air quality. It is widely acknowledged that atmospheric pollutants negatively impact human health; the same is also true for the health of wildlife and plants exposed to these pollutants (Brunekreef & Holgate, 2002; EEA, 2019; Schiavoni, et al., 2017). Pollen and seed formation of flowering plants have been affected when grown in areas of poor air quality (Azzazy, 2016; Sénéchal, et al., 2015). The purpose of this research was to assess pollen of Hedera helix (ivy), a native Irish wildflower (Devlin, 2019), growing in roadside habitats exposed to vehicular pollutants. Samples were collected in Sligo and Dublin; the anthers were removed from the flowers and dried at room temperature for 24 hours. The pollen was shaken from the dried anthers and mounted on to slides. Pollen grains were then observed under a compound light microscope and comparison microscope. Shape and size of the pollen grains were quantified. The findings were compared to typical shapes and sizes of H. helix pollen grains, found in literature and online pollen databases (Halbritter, 2016; PalDat, 2015). The results obtained from the study were examined in conjunction with air quality monitoring data from relevant local authorities and data from traffic count databases, to estimate the impacts of pollutants on pollen. Due to limited data available from the local authorities, no definite relationship between atmospheric pollutants and pollen grain shapes and sizes was established in this study. Proxy data was however used to be representative of the pollen sample sites, based on road density, traffic flow and nearby green space. Despite being preliminary work, the findings of this study showed variations exist between samples collected at different sites, either due to pollutant exposure or other environmental factors. This study also highlighted the current air quality monitoring situation in the Dublin and Sligo areas where the samples were collected.